An unusual case of vomiting and arthritis: A diagnostic enigma - Shivraj Padiyar; Daisy Doley; Ramesh Babu; John Mathew (Indian Journal of Rheumatology)
Sarcoidosis is a multisystem inflammatory disorder, which can have a myriad of presentations, with atypical presentation not being uncommon. Unless the clinician has a strong suspicion of sarcoidosis, it can be easily missed out. Here, we present an interesting case of a 44-year-old gentleman who had presented with inflammatory arthritis and vomiting. His serum cortisol levels were low. On further evaluation, he was found to have panhypopituitarism. Magnetic resonance imaging brain showed infiltrative disease involving the pituitary stalk. Imaging of the chest revealed mediastinal nodes which showed nonnecrotizing granulomatous inflammation on histopathology. After ruling out infectious causes a diagnosis of sarcoidosis was made, and the patient had a full recovery with steroids and methotrexate. Sarcoidosis can be a great mimicker presenting with a myriad of complications. Clinicians must be aware of the atypical presentations to diagnose the disease earlier.